Pharmacological perspective: glycyrrhizin may be an efficacious therapeutic agent for COVID-19 - Luo, Pan (Int J Antimicrob Agents, 2020)
Coronavirus disease 2019 (COVID-19) caused by the previously unknown pathogen, severe acute respiratory syndrome-related coronavirus-2 (SARS-CoV-2) is now a global pandemic. There are no vaccines or specific treatments against this new virus; therefore, there is an urgent need to advance novel therapeutic interventions for COVID-19. Glycyrrhizin is a triterpene saponin with various biological functions and pharmacological effects. This brief article discusses the therapeutic potential of glycyrrhizin for the treatment of COVID-19 from the perspective of its pharmacological action, including binding angiotensin-converting enzyme II (ACE2), downregulating proinflammatory cytokines, inhibiting the accumulation of intracellular reactive oxygen species (ROS), inhibiting thrombin, inhibiting the hyperproduction of airway exudates, and inducing endogenous interferon.